Venom of prey-specialized spiders is more toxic to their preferred prey: A result of prey-specific toxins - Pekár, Stano; Líznarová, Eva; Bočánek, Ondřej; Zdráhal, Zbyněk (The Journal of animal ecology, 2018)
In specialized predators, a variety of adaptations have evolved to such a level of specificity that they allow very effective exploitation of focal prey. Venom is an essential adaptive trait of predatory venomous species, such as spiders, yet our knowledge of spider venom is incomplete. In agreement with the prey preference hypothesis, we expected that the venom of spider specialists should be more toxic to focal than to alternative prey, because it is composed of prey-specific toxins. Here we used spiders with three types of trophic specializations: specialists that were ant-eating, termite-eating and spider-eating. We compared the efficacy of prey capture of preferred and alternative prey (measured as paralysis latency) with that of related generalists and profiled the venom of the studied species using proteomic methods. We used 22 spider species: six myrmecophagous, two termitophagous, three araneophagous and 11 euryphagous generalist species belonging to different families. We found that ten of the eleven specialist species induced significantly shorter paralysis latency in preferred prey than in alternative prey. Generalists exhibited either similar efficiency on both prey types or slightly higher efficiency on preferred prey. Multivariate analysis of proteomic profiles (peptides and proteins) revealed significant differences between trophic specializations, particularly in peptides. Specialists appear to have venom composed of unique specific compounds as revealed by the multivariate ordination and indicator analysis. These components are likely prey-specific toxins.
Keywords: pavoučí jedy; predátorské chování; fyziologická adaptace; pavouci; Spider Venoms; Predatory Behavior; paralysis; Animals; venom composition; specialization; capture efficacy; zvířata; Araneae; Spiders; Proteomics; proteomika; adaptation; Adaptation, Physiological